Pengaruh Tingkat Pendidikan Dan Jumlah Penduduk Terhadap Pengangguran Di Provinsi Lampung - Amanda; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to examine the effect of education level and population on unemployment rate in Lampung Province by using panel data regression approach. The estimation models used are Fixed Effect Model (FEM) and Random Effect Model (REM). Based on the test results, the REM model is considered the most appropriate. The main findings show that the level of education has a negative and significant influence on the unemployment rate, while the population has a positive and significant impact. Thus, efforts to improve the quality of education and control the population growth rate are needed to reduce the unemployment rate in the region.